AN ERROR ANALYSIS OF LEXICOGRAMMATICAL FEATURES IN STUDENTS’ WRITING EXPLANATION TEXT ABILITY (A Study at the Fourth Semester English Department of Institut Pendidikan Tapanuli Selatan in 2018/2019 Academic Year) - Asriani Hasibuan; Mita Riski Yanti Ritonga (Journal MELT (Medium for English Language Teaching), 2019)
The purposes of the research are to know the students’ error on using lexicogrammatical features in writing explanation text ability at the Fourth Semester of English Department of Institut Pendidikan Tapanuli Selatan and to know why the students made errors in using lexicogrammatical features in writing explanation text ability. The method which is used in this research is mixed method. The informants of this research are the fourth semester of English department which consisted of 15 students that was taken by using purposive sampling. Purposive sampling is used to get the informants by using certain criteria, where in this research the writer got the informants by error criteria. The instruments are used in this research are test, observation and interview. The lexicogrammatical features error analysis of students has done into three elements, they are: simple present tense, conjunction and passive voice. The result of data description shows that simple present tense was the error which most dominant that is made by the students. It took 63.0% of the total errors. Moreover, 23.0% error in conjunction used and 13.8% errors in passive voice. The causes of students’ errors in using lexicogrammatical features are lack of understanding about simple present tense, conjunction and passive voice; lack of awareness; interference of first language; carelessness (lack of motivation) and translation